Treatment of Knee Osteoarthritis and Chondral Injury with Umbilical Cord/Wharton’s Jelly-Derived Mesenchymal Stem Cells: A Systematic Review of Safety and Efficacy - Mohd Ishak-Samrin; Isa Naina-Mohamed; Mohamed S. Zulfarina; S. Fadilah Abdul Wahid; Ahmad Farihan Mohd Don; Norlelawati Mohamad; Muhamad Karbela Reza Ramlan; Akmal Hisham Md Yusoff Badrul (Journal of Functional Biomaterials)
Knee osteoarthritis (KOA) is a major cause of pain and disability worldwide, with no current treatment modality able to prevent the progressive destruction of articular cartilage. Mesenchymal stem cells (MSCs) have attracted interest in treating KOA and cartilage injury due to their self-renewal and multidirectional differentiation potential, as well as local bioactive factors with immunomodulatory and regenerative potential. This study aimed to evaluate the currently available studies using the intra-articular injection of Wharton’s jelly MSCs for KOA and cartilage injury. We analyzed all clinical trials published from inception to 31 December 2023. Six studies met the inclusion criteria, for a total of 97 patients and 134 knees. The follow-up period ranged from 3 to 48 months. There were no serious adverse effects noted. There was significant improvement in functional outcomes in the form of VAS, WOMAC, KOOS, and IKDC parameters, though radiological outcomes demonstrated mixed results. In conclusion, patients with KOA treated with intra-articular injections of Wharton’s jelly MSCs showed improvements in functional outcomes with no severe adverse effects. Multiple injections of Wharton’s jelly MSCs showed better outcomes compared to single-injection techniques. Wharton’s jelly MSCs may have potential as a cornerstone in the future treatment of KOA.